2021
DOI: 10.1038/s41598-021-83125-z
|View full text |Cite
|
Sign up to set email alerts
|

Early protein intake predicts functional connectivity and neurocognition in preterm born children

Abstract: Nutritional intake can promote early neonatal brain development in very preterm born neonates (< 32 weeks’ gestation). In a group of 7-year-old very preterm born children followed since birth, we examined whether early nutrient intake in the first weeks of life would be associated with long-term brain function and neurocognitive skills at school age. Children underwent resting-state functional MRI (fMRI), intelligence testing (Wechsler Intelligence Scale for Children, 5th Ed) and visual-motor processing (Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 43 publications
2
28
0
Order By: Relevance
“…However, according to randomized controlled trials, its long-term benefit for metabolism and neurological development is still unclear [ 39 , 40 , 41 , 42 ]. Nevertheless, data on associations between higher nutrient intake and improved growth suggest that parenteral nutrition in the first postnatal weeks is likely to improve cognitive outcomes [ 5 , 42 , 43 ].…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…However, according to randomized controlled trials, its long-term benefit for metabolism and neurological development is still unclear [ 39 , 40 , 41 , 42 ]. Nevertheless, data on associations between higher nutrient intake and improved growth suggest that parenteral nutrition in the first postnatal weeks is likely to improve cognitive outcomes [ 5 , 42 , 43 ].…”
Section: Parenteral Nutritionmentioning
confidence: 99%
“…Bacterial products and/or profibrous cytokines acting on cervical cells of the uterus may cause a change of MMPs expression. High concentrations MMP-8 of amniotic fluid are associated with PB (before the 32nd week of pregnancy) so induction of uterine contractions (directly or by functional "withdrawal" of progesterone) [50][51][52][53][54][55][56][57][58][59][60].…”
Section: Preterm Labor: the Mechanism Includesmentioning
confidence: 99%
“…The receptor antagonist of IL-1 inhibits the biological effects of IL-1, blocking its receptors. Consequently reduction of IL-1 production and induced from that of prostaglandin production by them endometrial tissue can prevent PB associated with infection Il-1β is found in chorionic villi, decidua, amniotic fluid and placental cultures [50][51][52][53][54][55][56][57][58][59][60]. Elevated levels of Il-6 are usually found in the amniotic fluid, with inflammation.…”
Section: Preterm Labor: the Mechanism Includesmentioning
confidence: 99%
See 2 more Smart Citations